2014
DOI: 10.4172/2375-4494.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Suicidality in Community Adolescents: A Brief Report

Abstract: We tested a theory-based model of suicidality in adolescents that included the variables: self-criticism, dependency, anger-temperament, depression and anger-in. A sample of 263 adolescents, 107 boys and 156 girls, aged between 15 and 19 years (M=16.8 , SD=1.26), from two high schools in the district of Évora, Portugal, responded to a socio-demographic questionnaire, to the Depressive Experiences Questionnaire for Adolescents (Blatt et al.), the Center for the Epidemiologic Studies of Depression Scale (Radloff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…According to Cantanzaro and Wei (53), this finding can be explained by the following scenario: individuals with higher levels of attachment anxiety tend to develop a negative internal working model of the self (45, 80) and to automatically engage in self-criticism and harsh self-evaluation with the aim of reducing the likelihood of being criticized by others (81). A suicidal attempt could be explained as the outcome of the emotional breakdown, which is a consequence of the failure of this strategy, particularly when others show critical or harsh attitudes (20), from which the individual concludes they are fundamentally worthless and do not deserve to live.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Cantanzaro and Wei (53), this finding can be explained by the following scenario: individuals with higher levels of attachment anxiety tend to develop a negative internal working model of the self (45, 80) and to automatically engage in self-criticism and harsh self-evaluation with the aim of reducing the likelihood of being criticized by others (81). A suicidal attempt could be explained as the outcome of the emotional breakdown, which is a consequence of the failure of this strategy, particularly when others show critical or harsh attitudes (20), from which the individual concludes they are fundamentally worthless and do not deserve to live.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined school problems, such as bullying or academic failure (7, 8), as well as interpersonal (9) and familial difficulties including frequent criticism, poor communication, perceived lack of support (10, 11), peer rejection, and low social support from friends (12). Still other studies have examined intrapersonal markers of risk, including impulsivity, rumination, hopelessness, mental pain (1316), hostility (17–19), and the presence of a chronic disease, particularly depression (20). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falgares et al (2017) found that dependency (as well as self-criticism) mediated the relationship between anxious attachment and suicidality in adolescents. Several studies with college students found that dependence and self-criticism predicted depression, which in turn predicted suicidality (Campos and Mesquita, 2014; Campos et al, 2014). Fehon et al (2000) found that, in a sample of adolescent inpatients with depression, both high levels of self-criticism and elevated levels of dependency were associated with suicidal behavior; however, dependent individuals were more likely to demonstrate an impulsive pattern of suicidal gestures and attempts, whereas those high in self-criticism were more likely to plan suicidal behavior.…”
mentioning
confidence: 99%